The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s12936-016-1136-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity among Plasmodium vivax isolates along the Thai–Myanmar border of Thailand

Abstract: BackgroundKnowledge of the population genetics and transmission dynamics of Plasmodium vivax is crucial in predicting the emergence of drug resistance, relapse pattern and novel parasite phenotypes, all of which are relevant to the control of vivax infections. The aim of this study was to analyse changes in the genetic diversity of P. vivax genes from field isolates collected at different times along the Thai–Myanmar border.MethodsTwo hundred and fifty-four P. vivax isolates collected during two periods 10 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 41 publications
2
12
1
Order By: Relevance
“…30 This may be in part due to lower transmission areas having increasing proportions of imported infections, which reflects the MOI and diversity of the infection origin, 22,69,70 and this effect would be enhanced for P. vivax by the fact that relapse can occur 1-3 years after the primary infection. 71 The high complexity of infection for P. vivax regardless of parasite prevalence is also comparable to other studies where high infection complexity and diversity were found even with sustained low parasite prevalence such as in South America 33,72,73 and Sri Lanka. 74,75 Polyclonal infections are common in malariaendemic areas of different countries for both species and can arise from a single mosquito bite carrying multiple clones or from inoculation by different mosquitoes carrying single clones.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…30 This may be in part due to lower transmission areas having increasing proportions of imported infections, which reflects the MOI and diversity of the infection origin, 22,69,70 and this effect would be enhanced for P. vivax by the fact that relapse can occur 1-3 years after the primary infection. 71 The high complexity of infection for P. vivax regardless of parasite prevalence is also comparable to other studies where high infection complexity and diversity were found even with sustained low parasite prevalence such as in South America 33,72,73 and Sri Lanka. 74,75 Polyclonal infections are common in malariaendemic areas of different countries for both species and can arise from a single mosquito bite carrying multiple clones or from inoculation by different mosquitoes carrying single clones.…”
Section: Discussionsupporting
confidence: 81%
“…This includes the ability to relapse, 71 the earlier appearance of transmission stages, lower density infections, and a faster acquisition of immunity, 3 the latter two of which may compromise diagnosis and subsequent treatment. Plasmodium vivax also has a wider geographical range due to its ability to develop within the mosquito vector at lower temperatures, 4 and at least in part due to a wider vector range in some endemic regions (though in PNG all local malaria vectors transmit both species).…”
Section: Discussionmentioning
confidence: 99%
“…Hha I digestion revealed 56 alleles and H1 allele was most prominent in the Indian sub-continent and was seen in the Type C variant among the Indian isolates. H1 allele in these variants has been reported from other regions of the world, including those from India [ 21 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the genetic diversity of malaria parasites from different regions is important for studies on population dynamics and is also valuable in discriminating parasite clones from infected individuals and tracing the origin of parasites [ 2 , 3 ]. Currently, several genetic markers have been used to study P. vivax populations’genetic diversity [ 4 7 ], the most popular being P. vivax merozoite surface protein 1 ( PvMSP-1 ). PvMSP-1 is an important protein for erythrocyte invasion, and thus vaccine research, which is encoded by the PvMSP-1 gene with approximately 1 720 amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies investigating the genetic diversity of P. vivax have focused on samples in a particular geographic region [ 6 , 7 , 12 , 18 ]. Only a few studies were implemented to compare samples from different regions.…”
Section: Introductionmentioning
confidence: 99%